Historical Course of Neuropsychiatric Effects of Lemon Balm (Melissa officinalis L.) as a Medicinal Herb - Javid Ghazizadeh; Reza Mohammadinasab; Nikolaj Travica; Saeed Sadigh-Eteghad; Mohammadali Torbati; Sanaz Hamedeyazdan; Ali Fakhari; Mostafa Araj-khodaei (Tabriz University of Medical Sciences, 2022)
Affective disorders have become prevalent and costly worldwide chronic conditions. Lemon Balm (Melissa officinalis L.) is a medicinal plant with beneficial effects on neuropsychiatric disorders. Its potential to specifically treat conditions such as depression and anxiety has been investigated for over 20 centuries. Given the lack of a historical overview of lemon balm in mood disorders, the present review aimed to introduce the historical course of the neuro-psychiatric applications of lemon balm across the centuries. We investigated several viable medieval Arabic sources up to the 15th century, to distinguish the neuropsychiatric applications, especially anxiolytic and anti-depressive effects of lemon balm. In the early centuries, lemon balm was mainly prescribed to treat gastrointestinal disorders. Over time, physicians identified the efficient use of lemon balm in sadness, sleep disorders, anxiety, depression, epilepsy, ischemic stroke, amnesia, sciatalgia, and radicular neuropathy. Importantly, it was established that the therapeutic effects of lemon balm in the field of neuro-psychiatric diseases were emphasized by physicians during the Middle Ages. These findings have since been validated in human clinical trials. Lemon balm has also demonstrated the ability to be utilized in epilepsy, amnesia and ischemic stroke. Based on the extensive history of lemon balm in neuropsychiatry, future investigations could use this knowledge to extensively investigate the potential of lemon balm in neuropsychiatric disorders such as depression and anxiety, and possibly develop an efficient neuropsychiatric remedy.